Geographical Analysis of Dams and Lakes and Their Role in Developing Water Tourism in The Kurdistan Region of Iraq: Dukan Dam and Lake - as a Case Study (Raparin Journal of Humanities (RJH), 2025)
The Kurdistan Region of Iraq is rich in numerous dams and lakes that can be invested in to develop water tourism, i.e., to utilize this potential to develop the tourism sector and compete with other economic sectors in the region, by activating them and enhancing their role within local tourism and encouraging tourists to practice its activities, especially water sports, such as swimming, rowing, and diving. The importance of the study lies in its efforts to encourage the Kurdistan Regional Government and relevant authorities to develop water tourism in the Dukan Dam and Lake, which will lead to the revitalization of tourism both domestically and internationally. This study also aims to identify the most important obstacles and problems facing the process of developing water tourism in the “Dokkan Dam and Lake”, and then to develop proposals that contribute to making it a distinguished site that attracts tourists and visitors to practice water tourism activities in particular. Since the development of water tourism leads to the activation and revitalization of water sports, therefore, in order to achieve the objectives of this hypothesis, the historical, descriptive and analytical approach was used alike, with division into four axes as follows:The first axis defined the study area and its location, while the second axis addressed the geographical distribution of dams and lakes in the Kurdistan Region of Iraq. The third axis was devoted to studying the importance of dams and lakes in water tourism development. The fourth axis addressed the obstacles to water tourism development and development methods in the dam and Lake Dukan. In conclusion, the study reached several conclusions, most notably that all lakes in the Kurdistan Region are considered artificial lakes. The most important recommendation was to conduct regular and continuous monitoring of Lake Dukan to ensure its cleanliness and lack of pollution.